Developing a Robust Acquisition System for Fringe Projection Profilometry (2019)
Since Fringe Projection Profilometry (FPP) is an intensity-based coding strategy, it is prone to improper optical setup arrangement, surface texture and reflectance, uneven illumination distribution, among others. These conditions introduce errors in phase retrieval which lead to an inaccurate 3-D reconstruction. In this paper, we describe a dynamic approach toward a robust FPP acquisition in challenging scenes and objects. Our aim is to acquire the best possible fringe pattern image by adjusting the object closer to an ideal system-object setup. We describe the software implementation of our method and the interface design using LabVIEW. Experimental results demonstrate that the proposed method greatly reduces sources of error in 3-D reconstruction. © Published under licence by IOP Publishing Ltd.